Caribbean Report 02-04-1990 - Whitehorne, Pat (anchor); Binnendijk, Chandra van (correspondent); Luchmon, Jagernath (interviewee); Baptiste, Sandra (correspondent); Williams, Philip (interviewee); Clarendon, Hannah (interviewee); Chand, Kamal (interviewee); Khan, Sharief (correspondent); Clarke, Lorna (correspondent); Hubert, Peter (interviewee) (The British Broadcasting Corporation, 1990)
Concerns arise in Suriname over the increase in drug trafficking after the recent capture of a batch of cocaine with an estimated street value of over US$20 million. Comments are expressed on Suriname becoming an important factor in international drug trafficking from South America to Europe, and the disruption of the ongoing peace process in the light of the recent drug events. Following the Financial News, questions are posed over the preparedness of the Caribbean countries to penetrate the highly competitive trading block of the future European Single Market. At a meeting in London, constraints are identified by export promotion officials as ranging from a lack of adequate infrastructure to inefficiency in the Caribbean manufacturing sector. The next segment reports that the sugar industry in Guyana could experience further crisis after a decision by the major sugar union to hold a two-day strike. The industrial action is in response to a collapse of talks with Guyana Sugar Corporation (GuySuCo) over wage claims. The report concludes with the voicing of concerns by black lawyers in Britain over the failure of the government to effectively tackle racism within the criminal system. The Society of Black Lawyers is calling for an anti-racism strategy to be implemented before the enactment of the new amendment outlawing legal discrimination against black barristers and offenders.
1. Headlines (00:00-00:41)
2. Increase in drug trafficking in Suriname. Chandra van Binnendijk reports from Paramaribo and Pat Whithorne interviews Jagernath Luchmon, Chairman of Surimane's National Assembly (00:42-05:35)
3. Financial News (05:36-06:26)
4. Are Caribbean countries ready to penetrate the European Single Market? Sandra Baptiste interviews Philip Williams, Executive Director of the Barbados Export Promotion Corporation and Hannah Clarendon, General Manager of the Dominican Import/Export Agency (06:27-09:22)
Keywords: Drug traffic -- Suriname.; European Economic Community -- Caribbean Area.; Foreign trade promotion -- Caribbean Area.; Sugar trade -- Guyana.; Strikes and lockouts -- Sugar industry -- Guyana.; England -- Lawyers -- Race relations.; Lawyers -- Race identity -- England.